2022
DOI: 10.1049/mia2.12284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electromagnetic scattering from typical targets for orbital‐angular‐momentum waves: Theoretical model

Abstract: The target scattering characteristics in microwave band are necessary to be researched for Orbital‐Angular‐Momentum (OAM) wave‐based radar applications. A theoretical description of electromagnetic (EM) scattering from a typical target by OAM waves is proposed in this paper. First, OAM waves are decomposed into plane waves in the spectral domain with different elevation and azimuth angles. Then, the scattering form of each decomposed plane wave is determined through coordinate system transformation and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Based on our previous work, the electric field of vortex waves can be decomposed into the superposition of plane waves with different elevation angle, α , and azimuthal angle, υ , which determines the propagation direction of decomposed plane waves. The transverse electric field of the incident vortex beams can be expressed as [21]…”
Section: Vortex Wave Scattering Model From a Rough Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous work, the electric field of vortex waves can be decomposed into the superposition of plane waves with different elevation angle, α , and azimuthal angle, υ , which determines the propagation direction of decomposed plane waves. The transverse electric field of the incident vortex beams can be expressed as [21]…”
Section: Vortex Wave Scattering Model From a Rough Surfacementioning
confidence: 99%
“…In our previous work, we obtained approximate numerical results of typical targets by plane wave expansion and coordinate system transformation [21]. Studying the scattering of vortex beams from rough surfaces may bring new insights into the vortex wave-matter interaction as well as new applications.…”
Section: Introductionmentioning
confidence: 99%
“…Later in 2022, the scattering characteristics of a vortex beam incident on a metallic sphere [30] and an electrically large aircraft [31] were investigated using the physical optics (PO) method in conjunction with the angular spectrum expansion method. Zhang et al [32] analyzed in detail the theoretical scattering of OAM waves incident on typical targets; in particular, they simulated and analyzed the scattering characteristics of a perfect electric conductor and dielectric targets. It was found that the target RCS was greater for vortex-beam incidence than for plane-wave incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Z. Wu studied the scattering characteristics of targets under vortex beams and concluded that the characteristics of targets were different when changing the OAM mode [20]. Compared with plane beams, vortex beams improve the ability of information acquisition and target detection [21][22][23]. B. Tang found that OAMs can carry more information than plane waves when passing through the chaff clouds [24].…”
Section: Introductionmentioning
confidence: 99%